Significações acerca do currículo formador - egressos(as) do curso de licenciatura em Educação Física - Lopes, João Pedro Goes (2019)
The present work has as its central problem the meanings of undergraduates in the initial formation in Physical Education about their educational curriculum, from the perspective of the theoretical framework of Cultural Studies in its poststructuralist version. Initially, there is a contextualization of higher education in Physical Education demonstrating its growth, as well as the expansion of this educational level in Brazil - with emphasis on private higher education. Language gains central prominence and it is from it that one explores the concept of culture and that of meanings. The methodology was based on two main moments: document analysis and semi-structured interviews with four graduates from two private institutions in the interior of São Paulo. The documentary analysis uses as a subsidy the Pedagogical Political Project of each institution in which the graduates studied were formed, as well as the analysis of the National Curriculum Guidelines of the Physical Education courses, which establishes directives to the training courses of this institution. modality. It is emphasized its importance in generating data for analysis, as well as to support the construction of the script of semi-structured interviews, for which graduates who work in the field of Physical Education degree were selected and, based on their speeches. , analyzed specific meanings about your training curriculum. Regarding the documentary analyzes performed, we discuss firstly the formation and identification of the authors; the strong concern with the practical issue of the course; the lack of specificity in the definition of the field and their expectations regarding the aptitude of the graduates to work in education. With the analysis of the semi-structured interviews, the meanings shared by the graduates reveal that the degree, in relation to the bachelor, is always allocated in a less prominent space; which has a close connection with the market logic propagated by the curricular organization - the appeals are always for the constant movement (of the students and graduates or the curriculum itself), to the lag and incompleteness of the initial formation. “Always” and for individualism (for merit or failure); culminating in what is conventionally called the Salvationist continuum. It concludes by pointing out the gaps of the initial formation, the preponderance of the market logic and the weakness of the subjects related to the degree.